Glas mora kojega (ne)ima - Pinter, Kornelija (Anafora, 2016)
The paper analyzes contacts of textual structures with the pannonian landscape in Delimir Rešicki's poetry. Its particular focus, speaking thematically, is the author's constant poetic dialogue with water which has disappeared. His textual correlation with water suits the panonnistic concept of literature which describes its geological history. Rešicki built his poetry around the fading water motif which has roots in reality, thus, reality in his poetry is this paper's indirect interest.